1995
DOI: 10.1073/pnas.92.18.8328
|View full text |Cite
|
Sign up to set email alerts
|

Rapid endocytosis coupled to exocytosis in adrenal chromaffin cells involves Ca2+, GTP, and dynamin but not clathrin.

Abstract: Rapid endocytosis (RE) occurs immediately after an exocytotic burst in adrenal chromaffin cells. Capacitance measurements of endocytosis reveal that recovery of membrane is a biphasic process that is complete within 20 sec. The ultimate extent of membrane retrieval is precisely controlled and capacitance invariably returns to its prestimulation value. The mechanism of RE specifically requires intracellular The physiological and molecular basis of secretion has been studied in some detail (1), but the nature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

43
302
3
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(350 citation statements)
references
References 36 publications
43
302
3
2
Order By: Relevance
“…Alternatively, the resealing process may require the recruitment of a dedicated fission machinery either before or after exocytosis. The endocytic protein dynamin has been proposed to serve this function (10,14,39). Two-color evanescent-field microscopy seems well suited to test this idea and to test for the transient recruitment of other proteins to spatially defined sites in the plasma membrane (22).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the resealing process may require the recruitment of a dedicated fission machinery either before or after exocytosis. The endocytic protein dynamin has been proposed to serve this function (10,14,39). Two-color evanescent-field microscopy seems well suited to test this idea and to test for the transient recruitment of other proteins to spatially defined sites in the plasma membrane (22).…”
Section: Discussionmentioning
confidence: 99%
“…20^30 s (Ryan et al 1996;Wu & Betz 1996). This is at least half of the total recycling timeöfar slower than endocytosis in other secretory systems (Thomas et al 1994;Artalejo et al 1995;Smith & Neher 1997;Engisch & Nowycky 1998). It seems paradoxical that the neurosecretory terminals that might bene¢t the most from rapid endocytosis do not appear to take advantage of such a mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrastructural studies have shown that dynamin I forms rings at the neck of clathrin-coated pits, and it has been hypothesized that a conformational change of the ring that correlates with GTP hydrolysis represents a key step leading to vesicle fission from the plasmalemma (6,7). In addition, dynamin I has also been implicated in rapid endocytosis, a form of Ca 2ϩ -triggered endocytosis detectable by capacitance measurement in neuroendocrine cells (8). Dynamin isoforms (dynamin II and dynamin III) are expressed in non-neuronal cells (9 -11) where they are thought to play a general role in clathrin-mediated endocytosis (12,13).…”
mentioning
confidence: 99%